Embodied politics and extreme disgust: an investigation into the meanings of bodily order and bodily disorder, with particular reference to the work of William Burroughs and David Cronenberg - Eadie, Jo (1998)
This thesis is an analysis of the ways in which images of bodily disgust function in social conflicts. It considers the necessary embodiment of political struggle: that is, the ways in which inequalities are sustained and contested through the material forms taken by human bodies and the meanings attached to bodily states. In chapter one I map out the theoretical grounding for an inquiry into embodiment, by showing how the physical forms taken by bodies are produced by social practices. I argue that ‘the body’ should be seen as a biological product, a ‘body project’, regulated and transformed by its environment. This in turn leads me to a consideration of how such body-shapings sustain regimes of power through constructing for subjects physical forms which are designed to maintain existing systems of inequality. Through a reading of Michel Foucault’s work, I show how such bodies are also able to resist power by making use of the material and discursive structures which seek, but fail, to render them wholly submissive. In chapter two I look at the ways in which the body acts as a map of the psyche, producing a subject which understands itself in terms of its experience of its body parts. I also consider how the body acts as a social symbol, encoding anxieties about the society that it inhabits. By considering both psychoanalytic accounts, and the work of Mary Douglas, I interrogate how concepts of order, form, and integrity become central to embodied subjectivity. In chapter three I consider how, in the Naked Lunch Quartet, William Burroughs represents the body as under threat from repulsive external substances, and how his depiction of such substances in fact relies on a notion of body matter itself as repulsive. I will show how this results from his conceptualization of bodily materiality as antithetical to freedom, and I argue that by demonstrating the impossibility of escaping from acts of invasion and possession, Burroughs's texts in fact undermine the libertarian position that he adopts. In chapter four I develop this argument through a comparison with Julia Kristeva's concept of abjection. I suggest that his representation of abject bodies enables Burroughs to critique the invasive mechanisms of authority, but requires that he collude with the stigmatizing discourses of authority in order to adopt such a position. In particular I consider how this affects his representation of gender. In chapter five I show how David Cronenberg's Shivers may be read as a film that both sustains and critiques the notion of innate bodily disorder. I argue that this is derived from his reliance upon notions of a hierarchy of bodies derived from inequalities of race and class. In chapter six I develop this critique with a reading of Cronenberg's The Fly. I suggest that this film is much more explicit about the fact that bodily chaos is in fact a state experienced by the socially excluded. It offers a critique of the processes by which we are made to feel disgust at our bodies, suggesting that disgust inaugurates a logic of paranoid purification, which in fact impedes the possibilities of the acceptance of those bodies which fall outside certain social limits. Finally, in my conclusion, I look at how Cronenberg's Rabid might be seen as a compendium of the issues of embodied politics, and use this to suggest possible directions in which the work of this thesis might be extended.